Finding Form: Looking at the Field of Organizational Aesthetics - Taylor, Steven S.; Hansen, Hans (Journal of Management Studies, 2005)
abstract Organizational research has long focused on the instrumental sphere with its questions of efficiency and effectiveness and in recent decades there has been interest in the moral sphere with its questions of ethics. Within the last decade there has also emerged a field that draws on the aesthetic sphere of our existence in organizations. In this review we look at the field of organizational aesthetics in terms of content and method, suggesting four broad categories of organizational aesthetics research: intellectual analysis of instrumental issues, artistic form used to look at instrumental issues, intellectual analysis of aesthetic issues, and artistic form used to look at aesthetic issues. We then suggest how organizational scholars might pursue artistic aesthetic organizational research.